Cryptography and security services mechanisms and applications - Mogollon, Manuel (Cybertech Pub., 2007)
Today's information technology and security networks demand increasingly complex algorithms and cryptographic systems. Individuals implementing security policies for their companies must utilize technical skill and information technology knowledge to implement these security mechanisms. Cryptography and Security Devices: Mechanisms and Applications addresses cryptography from the perspective of the security services and mechanisms available to implement these services: discussing issues such as e-mail security, public-key architecture, virtual private networks, Web services security, wireless security, and the confidentiality and integrity of security services. This book provides scholars and practitioners in the field of information assurance working knowledge of fundamental encryption algorithms and systems supported in information technology and secure communication networks.